Analysis of central nervous system efficacy in the J-ALEX study of alectinib versus crizotinib in ALK-positive non-small-cell lung cancer. (July 2018) - Nishio, Makoto; Nakagawa, Kazuhiko; Mitsudomi, Tetsuya; Yamamoto, Nobuyuki; Tanaka, Tomohiro; Kuriki, Hiroshi; Zeaiter, Ali; Tamura, Tomohide
Highlights: Alectinib is the preferred first-line treatment option for ALK -positive NSCLC. Alectinib showed superior efficacy to crizotinib in the J-ALEX phase III study. We assessed CIRs of CNS progression, non-CNS progression and death in J-ALEX. Alectinib prevented CNS progression in patients with baseline CNS disease. Alectinib prevented onset of new CNS lesions in patients without baseline CNS disease. Abstract: Objectives: We determined the central nervous system (CNS) efficacy of alectinib by calculating time to CNS progression and cumulative incidence rates (CIRs) of CNS progression, non-CNS progression and death in patients with anaplastic lymphoma kinase ( ALK )-positive non-small-cell lung cancer (NSCLC) enrolled in the J-ALEX phase III study. Materials and methods: Japanese patients aged ≥20 years with ALK -positive NSCLC who were ALK inhibitor-naïve and chemotherapy-naïve, or who had received one previous chemotherapy regimen, were enrolled. Patients with treated or untreated asymptomatic CNS metastases were eligible. Treatment comprised oral alectinib 300 mg twice daily or crizotinib 250 mg twice daily until progressive disease, unacceptable toxicity, death or withdrawal. Imaging scans (computed tomography/magnetic resonance imaging) were taken at baseline and at regular intervals throughout the study. The CIRs for CNS progression, non-CNS progression and death were calculated for patients with and without baseline CNS metastases using a competing risks method. Results: The hazard ratio for time to CNS progression in patients with and without baseline CNS metastases was 0.51 (95% confidence interval [CI]: 0.16–1.64; P = 0.2502) and 0.19 (95% CI: 0.07–0.53; P = 0.0004), respectively. The CIRs of CNS progression and non-CNS progression were lower in the alectinib group than in the crizotinib group at all time points. The 1-year CIRs of CNS progression were 16.8% and 5.9% with crizotinib and alectinib, respectively, and the 1-year CIRs of non-CNS progression were 38.4% and 17.5%, respectively. Comparable findings were obtained in patients with or without baseline CNS metastases. Conclusion: Alectinib appears to avert the progression of CNS metastases in patients with ALK -positive NSCLC and baseline CNS metastases, and to prevent the development of new CNS lesions in patients without baseline CNS disease.